Wrestling is a Kind of Sport with an Example of the First Training jar the Importance of the Formation of FastPaced Power Attributes with the Help of Moving Games - M.B.Toshboyeva (Zien Journals, 2022)
Quick - force qualities in children with reduced mobility in the fight circle help to increase the effectiveness of development with the help of traditional standard exercises and specially selected moving games. In this article, we will talk about the importance of the formation of operational power attributes with the help of moving games in the process of preliminary training on the example of wrestling sports.
Keywords: fight; action games; formation; development